The Impact of Community Health Education Media in the Industrialization Era on the Diet of High Risk Pregnant Women - Yusriani, Yusriani; Septiyanti, Septiyanti (Universitas Negeri Semarang, 2021)
Nutritional problems are still a global problem throughout the world. Media is one of the things that needs to be considered in conducting health promotion as an impact of the industrial era. This study aims to determine the effect of health education media in the industrial era on changes in behavior of pregnant women at high risk in dietary care. This research was carried out in the Work Area of the Makassar City Kassi-kassi Health Center. This research is a quasi-experimental quantitative type with a non-equivalent control group design using a purposive sampling method. The population in this study were pregnant women which consisted of 214 pregnant women. The sample size in this study was 40 pregnant women in the experimental group and 40 pregnant women in the control group. Data collection uses the observation method, interviews using a pre and post test questionnaire in the group The intervention was given a community health education media in the form of audio visual aids, namely video and in the control group a visual education aid was provided in the form of visual aids, namely a poster. Data analysis using Wilcoxon test and Mann Whitney test. The results of the study using the Wilcoxon test found that the media of health education in the form of effective videos of changes in the care of eating patterns of high risk pregnant women (p value 0.005). While health education media such as posters did not affect the change in care of diet for high-risk pregnant women (p value 0.005). Research novelty found that in the industrialization era audio visual (video) media is more effective than visual media (posters) in community health education. Extension needs to be done by using videos so that the eating patterns of pregnant women are at high risk of becoming better.